Hubungan Kadar Soluble Intercellular Adhesion Molecule-1 dan Soluble Vascular Cell Adhesion Molecule-1 dengan Gradasi Trombosis Atrium Kiri pada Stenosis Mitral - Elen Elen; Pramono Sigit; Yoga Yuniadi; Ismoyo Sunu (Jurnal Kardiologi Indonesia, 2015)
Background. The relationship between inflammation and coagulation has been widely described, which adhesion molecules play important role in inflammation. Soluble intercellular adhesion molecule-1 (sICAM-1) and soluble vascular cell adhesion molecule-1 (sVCAM-1) seem to be related to thrombosis in few previous studies. The level of those molecules were increased in mitral stenosis (MS), however their relationship with left atrial thrombosis gradation is still unknown.Methods. Patients with moderate-severe MS (without any significant mitral regurgitation) who underwent transesophageal echocardiography were recruited consecutively in September-October 2013. They were divided into 3 categories of left atrial thrombosis gradation: non-thrombus without dense left atrial spontaneous echo contrast (LASEC) group, and non-thrombus with dense LASEC group, and thrombus group.Results. A total of 39 subjects were enrolled in the study with a mean age of 40.97±9.61 year. Moreover, 71.8% of them were female and 67.7% of them had atrial fibrillation (AF). Evaluation on left atrial thrombosis gradation as mentioned above showed that sICAM-1 levels were 284.74 (218.79-321.00) ng/mL, 346.86 (125.68-698.12) ng/mL, and 395.93 (171.44-1021.53) ng/mL, consecutively (p=0.280). While sVCAM-1 levels gradually increased based on those groups consecutively: 729.01 (543.93-967.80) ng/mL, 1066.00 (581.36-2470.60) ng/mL, and 1158.00 (668.66-2498.30) ng/mL (p=0.016). Multivariate analysis showed that AF and mitral valve area (MVA) influence thrombosis gradation.Conclusion. Difference in sVCAM-1 levels were found among left atrial thrombosis gradation groups in mitral stenosis, but its effect on thrombosis gradation was influenced by AF and MVA.